Do environmental taxes and renewable energy consumption play a role in climate change mitigation? International evidence from developing economies - Ayoub Rabhi; Ismail Soujaa; Brandon Parsons (Research in Globalization, 2024)
Climate change and environmental degradation are largely attributed to increased carbon dioxide emissions (CO2). This study investigates the effectiveness of environmental taxes and renewable energy consumption on reducing CO2 emissions in 36 developing countries from 1994 to 2018, using the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) panel data methodology. Our findings indicate that renewable energy consumption plays a crucial role in lowering CO2 emissions, underscoring the need for increased investment in renewable energy infrastructure and technological advancements. Conversely, environmental taxes do not have a significant impact on emissions reduction in these countries, possibly due to inadequate implementation and institutional constraints. These findings suggest that policies promoting renewable energy, such as subsidies, incentives, and investments in research and development, are crucial for achieving meaningful emission reductions. Therefore, international efforts may be more effective by providing financial support and technological assistance rather than emphasizing environmental taxes, which may not be suitable for developing nations.
Keywords: 330; Climate change; CO2 Emissions; Environmental tax; Renewable energy; CS-ARDL Panel data